DAMPAK SOSIAL OMNIBUS LAW CIPTA KERJA PERSPEKTIF SOSIOLOGI HUKUM - Hanifah Az Zahra; Agus Machfud Fauzi (ADLIYA: Jurnal Hukum dan Kemanusiaan, 2021)
Government policies by legitimizing the presence of the omnibus law on copyright work, socially and legally have an impact on labor and workers. The reason is that this controversial law is considered to be very detrimental to labor and workers. The purpose of this study was to analyze the extent to which social impacts were generated after the government legal sociological perspective of the work copyright omnibus law was passed. This study uses a qualitative approach and descriptive methods and is equipped with literature study data collection. The results of the study conclude that the sociology of law responds to the rejection of the omnibus law on work copyright done by workers and labor because it will have an effect on social impacts that have implications for demonstrations of labor and workers nationally.